Dampak Pola Asuh Permisif Orangtua Terhadap Perilaku Remaja Perspektif Hukum Islam (Studi Kasus Di Medan Amplas Kota Medan) - Mustafa Parinduri; Irwan (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Parenting has an impact on children's attitudes and behavior in interaction. In providing these parenting activities, parents will provide attention, rules, discipline, rewards and punishments as well as responses to their children's wishes in order to avoid juvenile delinquency. The problem that occurs in Medan Amplas, Medan City is the existence of juvenile delinquency behavior. This is due to the loss of parental control over their children in parenting and educating their children. The purpose of this research is to find out how the impact of permissive parenting on adolescent behavior in Medan Amplas and how Islamic Law views permissive parenting. This type of research is empirical juridical with a living case studies approach and conceptual approach. Data is collected through interviews and document studies, then the data is processed and analyzed with qualitative methods. The results showed that permissive parenting characterized by a lack of parental supervision and guidance of children is not in accordance with parenting in the view of Islamic law because parents have the obligation to educate, guide, and prevent children from doing bad things.